Evaluasi Pembelajaran pada Keterampilan Menulis di Kelas Tinggi - Annisa Rahmadani; Irlyanova Sabina; Novita Sari Nasution; Juni Sahla Nasution (Badan Penerbit STIEPARI Press, 2024)
Writing skills are one of the main competencies that must be mastered by students in the upper grades of elementary school. This article discusses the evaluation of writing skills learning in elementary school classes. The purpose of this research is to explore the role of formative and summative evaluations, as well as authentic evaluations in improving students' writing abilities. The literature study method was used to collect information related to writing learning evaluation. The subjects of this research were elementary school students, with research objects including aspects such as sentence structure, vocabulary, and organization of ideas in writing. The research results show that evaluation of writing learning has an important role in improving students' writing skills. Evaluation helps in measuring student progress, provides appropriate feedback, supports instructional planning, and encourages reflection for both teachers and students. The implication of this research is the importance of carrying out systematic evaluations by educators in order to create a quality learning environment, especially in terms of improving students' writing skills in the upper grades of elementary school. Thus, this article provides valuable insight for educational practitioners in improving writing learning evaluation methods that are effective and have a positive impact on student development.